2011
DOI: 10.1002/chem.201102782
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis and Mutagenicity of Oligonucleotides Containing 5‐Hydroxymethylcytosine, 5‐Formylcytosine and 5‐Carboxylcytosine

Abstract: 5-Formylcytosine (fC or (5-CHO)dC) and 5-carboxylcytosine (caC or (5-COOH)dC) have recently been identified as constituents of mammalian DNA. The nucleosides are formed from 5-methylcytosine (mC or (5-Me)dC) via 5-hydroxymethylcytosine (hmC or (5-HOMe)dC) and are possible intermediates of an active DNA demethylation process. Here we show efficient syntheses of phosphoramidites which enable the synthesis of DNA strands containing these cytosine modifications based on Pd(0)-catalyzed functionalization of 5-iodod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
67
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 60 publications
(58 reference statements)
12
67
0
6
Order By: Relevance
“…It was hypothesized that the existence of such an intra-base hydrogen bond would shift the amino-imino equilibrium 48,52,53 , which would enable 5fC and 5caC to form two, instead of three, hydrogen bonds with an opposite guanine, equivalent to a G:T or G:U ‘wobble’ pair. Previously observed mutagenic potential of 5fC and 5caC in vivo and in vitro 49,52,53,54,55 suggested the possible existence of the imino tautomeric form. TDG might take advantage of the tendency of G:5fC and G:5caC to form a mismatch-like wobble hydrogen bonding pattern and turn them into substrates, whereas ROS1 is insensitive to mismatches.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was hypothesized that the existence of such an intra-base hydrogen bond would shift the amino-imino equilibrium 48,52,53 , which would enable 5fC and 5caC to form two, instead of three, hydrogen bonds with an opposite guanine, equivalent to a G:T or G:U ‘wobble’ pair. Previously observed mutagenic potential of 5fC and 5caC in vivo and in vitro 49,52,53,54,55 suggested the possible existence of the imino tautomeric form. TDG might take advantage of the tendency of G:5fC and G:5caC to form a mismatch-like wobble hydrogen bonding pattern and turn them into substrates, whereas ROS1 is insensitive to mismatches.…”
Section: Discussionmentioning
confidence: 85%
“…The four chemically modified forms of cytosine might not be genetically equivalent in terms of base pairing. A strong intramolecular hydrogen bond has been observed between the exocyclic N 4 amino group (NH 2 ) and the carbonyl oxygen (O=C) at ring carbon-5 position of 5fC, in the free nucleoside form 49,50 , and the carboxyl moiety (COO − ) of 5caC in the protein bound form 51 . It was hypothesized that the existence of such an intra-base hydrogen bond would shift the amino-imino equilibrium 48,52,53 , which would enable 5fC and 5caC to form two, instead of three, hydrogen bonds with an opposite guanine, equivalent to a G:T or G:U ‘wobble’ pair.…”
Section: Discussionmentioning
confidence: 99%
“…Base pairing of guanine and the imino tautomer of 5caC (Figure 3A) has the same geometry as a G·T mismatch37 and was suggested in a previous study38; the results of exonucleolytic degradation in our study may be attributed to this type of base-pair formation. Münzel et al demonstrated intramolecular hydrogen bonding between the amino and formyl groups of 5fC, but suggested that a substantial shift of tautomer equilibrium toward the imino form was unlikely27. Although it is very difficult to experimentally detect the unfavored imino tautomers of cytosine derivatives3940, electron-withdrawing substituents at the C5 position of cytosine may facilitate base pair formation with the minor tautomer because this type of substitution destabilizes the Watson–Crick G·C base pair41.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that 5fC and 5caC are enriched at gene regulatory elements in Tdg -deficient ES cells, suggesting the involvement of 5fC and 5caC in transcriptional regulation2324. Other studies have suggested 5fC induces G·C to A·T transition mutations during DNA replication when DNA polymerase encounters 5fC on template-strand DNA25262728. When 5fC and 5caC behave as mutagenic bases, TET protein-mediated consecutive oxidations of 5mC and 5hmC leads to deleterious consequences such as predisposition to cancer or apoptosis due to the accumulation of genomic mutations, unless 5mC oxidation is coupled with efficient elimination of 5fC and 5caC.…”
mentioning
confidence: 99%
“…20 This is in line with a previous in-vitro mutagenesis assay showing that 5fdC is only marginally mutagenic (1% C → T transition). 21 In this article, we assessed how these cytosine derivatives perturb the efficiency and fidelity of DNA replication in cultured human cells. Our results demonstrated that 5fdC and 5cadC but not 5hmdC could modestly inhibit DNA replication, though none of them could induce detectable mutations during replication in HEK293T cells; our results are in agreement with the roles of these modified nucleosides in epigenetic regulation.…”
Section: Introductionmentioning
confidence: 99%